(untitled) (Research, Society and Development, 2024)
Knowing the great tendency to reuse non-biodegradable and waste-forming solid waste to make new products today, thermoplastic recycling is well known. The low-temperature thermoplastic polymer is an alternative in the manufacture of various assistive technology devices, as it adds excellent combinations of mechanical properties. It is composed of cross-linked polycaprolactan (PCL) and polyurethane (PU). The study was set up using processes for the mechanical recovery of thermoplastics and a waste collection network with public and private hospitals, which promoted the reuse of discarded thermoplastic masks. In the normal cycle of use, masks used for their intended purpose are discarded as solid hospital waste. Based on the concept of Industrial Ecology, in line with the National Solid Waste Policy, studies and research into the reuse of this material are justified. The proposal is expected to reduce environmental and financial costs, adding advantages to the treatment of patients who would not have access to techniques like this. As a result, it is anticipated to be a viable technique for the manufacture of a waste product, for use in hospital contexts and with the potential to be used in hospitals belonging to the Brazilian Hospital Services Company (EBSERH). The aim is to contribute to minimizing environmental degradation processes, adding advantages in reducing public spending and collaborating in the treatment of patients in the SUS network.